Integrating spontaneous urban woodlands into the green infrastructure: Unexploited opportunities for urban regeneration. (March 2021) - Trentanovi, Giovanni; Campagnaro, Thomas; Kowarik, Ingo; Munafò, Michele; Semenzato, Paolo; Sitzia, Tommaso
Highlights: Spontaneous woodlands support a range of social, cultural and ecological services. Italian urban plans are deficient in spontaneous urban woodlands consideration. Recognition of spontaneous woodlands recognition in urban plans can support regeneration strategies. Citizens are pivotal to maintain and value spontaneous urban woodlands. Abstract: Urban forests have manifold social, economic, cultural and ecological benefits and are major components of the urban green infrastructure. Among them, spontaneous urban woodlands develop unintentionally on abandoned lands in both growing and shrinking cities and deserve additional attention. We aimed to describe the planning and social processes linked to failures and successes in recognising spontaneous woodlands in Italy. We collected data on the woodland area characteristics, urban settings, and former land use as well as on the planning and property evolution (e.g. land use zone designations) and citizens involvement for 19 sites in 13 representative Italian cities. Our results highlighted that spontaneous woodlands are heterogeneous in size and age, and grow on a variety of previous land uses, with residential and industrial being the most dominant. More than half of the urban plans designated land uses that require new soil sealing and tree plantations instead of maintaining the existing woodlands. Only in four case studies, urban plans recognised the spontaneous woodland, at least partially, as an element of the city's green infrastructure. We pinpoint an overall deficiency of the planning process in considering spontaneous urban woodlands, although with some exceptions that can represent models for future planning. The role of citizens seemed pivotal, even if not necessarily decisive, in the promotion and maintenance of these woodlands as a real social and ecological asset. A complex and modern array of approaches should capitalise on the potential benefits of spontaneous urban woodlands with the participation of citizens as a strong element of governance.